Bilateral shoulder arthritis in COVID-19 patient after prolonged mechanical ventilation assist - Neves, Teresa Resende (2021)
Prolonged immobilization and, in particular, mechanical ventilation, have been linked to muscle atrophy. Anecdotal reports in the literature describe rhabdomyolysis as a potential late complication of COVID-19 infection which, in severe cases, may coexist with fluid collections. We report a case of a 28-year-old patient that had been recently hospitalized with SARS-CoV-2 pneumonia, with need for invasive ventilation support. Days after being discharged, the patient presents with retrosternal thoracalgia irradiating to the left upper limb. On physical examination, abduction and external rotation were limited due to pain complaints and there was soft tissue swelling of the corresponding shoulder and arm. Imaging evaluation was essential to establish the underlying condition, revealing bilateral arthritis communicating with large rotator cuff collections, which was considered of septic nature.